Pengaruh Kombinasi Sagu Kukus (Metroxylon Spp) dan Tepung Keong Mas (Pomacea Spp) sebagai Pengganti Jagung Kuning terhadap Penampilan Itik Jantan Alabio, Mojosari dan Hasil Persilangannya (The Effect of Steaming Sago (Metroxylon Spp) and Golden Snail Meal - Ahmad Subhan; Tri Yuwanta; Jafendi Hasoloan Purba Sidadolog (Buletin Peternakan, 2010)
The aim of the experiment was to find out the effects of steaming sago (Metroxylon Spp) and golden snail meal (Pomacea Spp) combination for yellow corn substitution, on the performance of male Alabio, Mojosari, and their cross(MA). One hundred and ninety two young male ducks from the three breeds of 7 day old were assigned in 48 units of pens (4 ducks/pen). The experimental design was Completely Randomized Design with factorial (3x4) the first factorwas duck breeds (a) consisted of three duck breeds, Alabio, Mojosari, and Raja ducks, and the second factor was the type of ration of: R0 (control/100% basal ration), R1 (basal ration + 13% steaming sago and 2% golden snail flour), R2(basal ration + 26% steaming sago and 4% golden snail flour) and R3 (basal ration + 39% steaming sago and 6% golden snail flour). All treatments were repeated four times. The observed variables were the performance of ducks(body weight, body weight gain, ration consumption, and feed conversion ratio). The results indicated that breed had significant effects (P<0.05) on body weight, body weight gain, and ration conversion. Meanwhile, types of feed hadsignificant effects (P<0.05) on feed consumption, body weight gain, and final body weight. It was concluded that the combination of steaming sago and golden snail meal up to 45% of the ration could replace the need for yellow corn assource of energy without affecting the performance of male ducks of 1–8 weeks old. Cross male ducks were better than male Alabio and Mojosari ducks because they were more efficient in converting ration in to meat which resulting inhigher body weight gain.(Key words: Steaming sago, Golden snail flour, Male ducks, Performance)